A guerra comercial Estados Unidos e China: consequências na economia brasileira - Gabriel, João Tavano (2024)
This monography aims to elucidate the main consequences for Brazil of the Trade war between China and United States of America, as this event represent a significant milestone in the ongoing challenge between these global powers for the economic hegemony in the 21st century. Once the central point of the conflict has been characterized, it is evident that Brazil has gained advantages in the international soybean market. However, on a deeper level, there has been interference in the implementation of the 5G technology in the domestic market, which directly impacts Brazil’s insertion in the international scenery